Wokół profilaktyki onkologicznej. Charakterystyka uwarunkowań zachowań zdrowotnych kobiet objętych „Populacyjnym Programem Profilaktyki i Wczesnego Wykrywania Raka Szyjki Macicy”. Komunikat z badań - Piątkowski, Włodzimierz; Sadowska, Anna (Acta Universitatis Lodziensis. Folia sociologica, 2016)
The subject of the present analysis are health behaviors among women between 25 and 59 years of age and their determinants, which, simultaneously, constitute the social context for cervical cancer prevention in Poland. Among the factors which are of particular interest to the researchers, there are the following: life satisfaction (including: health, work, family and sex life), satisfactory life conditions, type and sources of social support, difficult life experiences, the amount of family and household responsibilities, lay definition of health, pro-health behaviors and health condition (judgment based on the medical evaluation). The present study also posed various questions concerning the availability and use of medical services (general practitioner, specialized doctor, dentist), genetic testing concerning cancer risk, gynecologist’s consultations and preventive smear tests. The conclusions presented below are based on the nationwide representative survey conducted as a part of the National Science Centre’s grant awarded for the implementation of the project entitled “The problem of women attending cervical smear tests in Poland. An attempt of the socio-medical analysis”. Quantitative research (questionnaire-based interviews, Computer Assisted Personal Interviewing, or CAPI) was conducted on the sample of 500 women aged 25–59 years, and aimed at reflecting various characteristics of the overall population of women involved in the Population Program of Prevention and Early Detection of Cervical Cancer (PPPWWRSM).